Anticancer effects of myricetin derivatives in non‐small cell lung cancer in vitro and in vivo - Mengmeng Li; Genlan Zha; Rujun Chen; Xin Chen; Qian Sun; Hao Jiang (Wiley, 2022)
Abstract Lung cancer is the most common cause of cancer‐related deaths. Moreover, exploring efficient tumor‐killing drugs is urgently needed. In our study, several derivative compounds of myricetin were synthesized and tested. Experiments on non‐small cell lung cancer (NSCLC) showed that S4‐2‐2 (5,7‐dimethoxy‐3‐(4‐(methyl(1‐(naphthalen‐2‐ylsulfonyl)piperidin‐4‐yl)amino)butoxy)‐2‐(3,4,5‐trimethoxyphenyl)‐4H‐chromen‐4‐one) had the strongest effect on A549 cell inhibition across all compounds. Furthermore, S4‐2‐2‐treated A549 cells were also suppressed when transplanted into immunodeficient mice. Particularly, we found that the migration and invasiveness of A549 cells became suppressed upon treatment with S4‐2‐2. Furthermore, the compound significantly induced cell apoptosis, but did not affect the cell cycle of A549 cells. Finally, we revealed that S4‐2‐2 inhibited the biological function of NSCLC cells by regulating the protein process in the endoplasmic reticulum, and then by inducing the expression of apoptosis‐related proteins. Taken together, S4‐2‐2 was shown to act as a potential molecular inhibitor of A549 cells.